1998
DOI: 10.1101/gad.12.10.1539
|View full text |Cite
|
Sign up to set email alerts
|

The competence transcription factor of Bacillus subtilis recognizes short A/T-rich sequences arranged in a unique, flexible pattern along the DNA helix

Abstract: The development of genetic competence in Bacillus subtilis is regulated by a complex signal transduction cascade, which leads to the synthesis of the competence transcription factor (CTF). Previous studies suggested that CTF is encoded by comK. ComK is required for the transcription of comK itself, as well as of the late competence genes encoding the DNA uptake machinery and of genes required for homologous recombination. Here, we used purified ComK to study its role in transcription and to determine the DNA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
156
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(163 citation statements)
references
References 44 publications
5
156
2
Order By: Relevance
“…ComK itself activates the transcription of comK. It has previously been shown that ComK binds upstream of the comK transcription initiation site, where it presumably recruits the RNA polymerase (19). Since DegU also binds to the comK promoter, we tested whether DegU might enhance the binding of ComK.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…ComK itself activates the transcription of comK. It has previously been shown that ComK binds upstream of the comK transcription initiation site, where it presumably recruits the RNA polymerase (19). Since DegU also binds to the comK promoter, we tested whether DegU might enhance the binding of ComK.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been shown that ComK operates as a double dimer, in which each dimer recognizes a dyad symmetrical consensus sequence (AAAAN 5 TTTT), the AT-box (19). In the comK promoter, the distance between the two AT-boxes is 44 bp.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transformation competence in bacteria and meiosis in eukaryotes are both differentiated states for generating genetic variation via homologous recombination, and both are bona fide developmental processes. In the well-studied cases of Bacillus subtilis and Sacharomyces cerevisiae the induction of competence (Hamoen et al 1998) and meiosis (Chu et al 1998), respectively, are triggered by nutritional exhaustion and/or cell crowding. To a first approximation, homologous recombination is equally probable anywhere along DNA sequences that are similar (first formulated by JBS Haldane).…”
Section: Developmental and Physiological Themes In Evolutionmentioning
confidence: 99%